Dedicated Bioenergy Crops and Water Erosion. Issue 2 (1st March 2019) - Acharya, Bharat Sharma; Blanco‐Canqui, Humberto; Mitchell, Robert B.; Cruse, Richard; Laird, David
Abstract : Information on the water quality impact of perennial warm‐season grasses (WSGs) when grown in marginal lands as dedicated energy crops is limited. We studied how WSGs affected runoff, sediment, and nutrient losses and related near‐surface soil properties to those of no‐till corn ( Zea mays L.) on an eroded soil in southwestern Iowa and a center pivot corner in east‐central Nebraska. The experiment at the eroded soil was established in 2012, and treatments included 'Liberty' switchgrass ( Panicum virgatum L.) and no‐till continuous corn. The experiment at the pivot corner was established in 2013 with 'Liberty' switchgrass, 'Shawnee' switchgrass, low‐diversity grass mixture, and corn. We simulated rainfall at 63.5 ± 2.8 mm h −1 for 1 h to portray 5‐yr return periods and measured water erosion in spring 2017. Time to runoff start and runoff depth did not differ between WSGs and corn. On the eroded soil, sediment and nutrient losses did not differ between treatments. At the pivot corner, sediment (0.71 vs. 0.15 Mg ha −1 ) and PO4 –P (0.037 vs. 0.006 kg ha −1 ) losses were five times higher in corn than in WSGs. Near‐surface soil properties did not differ on the eroded soil, but at the pivot corner, wet aggregate stability was four times higher and residue cover was 34% higher in WSGs than in corn. Water‐stable aggregates were negatively correlated with NO3 –N and PO4 –P losses. Overall, WSGs can improve water quality in marginally productive croplands, but their effectiveness appears to be site specific. Core Ideas: Warm‐season grasses did not reduce runoff depth compared with corn. Warm‐season grasses on a center pivot corner reduced sediment and nutrient loss compared with corn. Sediment loss between corn and switchgrass grown in an eroded soil did not differ. Warm‐season grass effectiveness to reduce water erosion can be site specific.